Android Game HUPROSED (Human Reproductive System and Sex Education) as Learning Media on Human Reproductive System Topic - Putri Sekar Melati; Eka Cahya Prima; Eliyawati Eliyawati (Universitas Pendidikan Indonesia, 2023)
The topic of the Human Reproductive System integrated with comprehensive sex education was selected for this research because the concept of the human reproductive system is highly related to daily life. This study aims to develop an Android game application named